2021
DOI: 10.5644/ama2006-124.302
|View full text |Cite
|
Sign up to set email alerts
|

Combined Microsurgical, Endoscopic and Neuronavigation Assisted Transseptal-Transsphenoidal Resection of Pituitary Tumors

Abstract: <p><strong>Objective. </strong>To describe the technical nuances of multimodal transseptal-transsphenoid surgery for pituitary tumors using a combination of microneurosurgery, neuroendoscopy, and electromagnetic neuronavigation.</p><p><strong>Materials and Methods. </strong>A transnasal approach to the sella is performed endoscopically and widely exposed by an otolaryngologic surgeon. Surgery is next performed by the neurosurgeon with microscope and  neuronavigation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Our analysis has shown that the use of iMRI is beneficial for surgery, regardless of the type of mirror and field strength. Additionally, Pojskić et al ( 3 ) considered that the two mirrors were complementary and recommended that both mirrors could be used to optimize the minimally invasive surgical technique. Regarding the selection of field strength, we found little difference among different MRI field strength subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis has shown that the use of iMRI is beneficial for surgery, regardless of the type of mirror and field strength. Additionally, Pojskić et al ( 3 ) considered that the two mirrors were complementary and recommended that both mirrors could be used to optimize the minimally invasive surgical technique. Regarding the selection of field strength, we found little difference among different MRI field strength subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Pituitary tumor represents a common intracranial pathology and pituitary neuroendocrine tumor (PitNET) is the most common type of pituitary tumor, in which usually hormones are abnormally secreted and systematic upwards compression of optic structures occurs, resulting in a wide variety of clinical sequelae ( 1 , 2 ). Transsphenoidal surgery (TSS), known for its simplicity and minimal invasiveness, is widely embraced as the primary treatment for most PitNET cases, with both the endoscope and microscope yielding satisfactory clinical outcomes ( 3 , 4 ). For PitNET, gross total resection (GTR) has been found to significantly reduce the chances of recurrence is the surgical ideal target ( 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tension (T) over the nerve was calculated using a mathematical equation derived from simple cable mechanics: T = WL/4d (Figure 4). 12,13 We compared forces, dips, and nerve tensions between superior and lateral pulls and after all 3 mobilizations. Statistical analysis was performed using the Student t test with significance set at P ≥ .05.…”
Section: Methodsmentioning
confidence: 99%
“…3-9 Furthermore, iatrogenic ON injury may occur during surgery through direct mechanical damage, improper manipulation, heat or vibration transmission, or interruption of vascular supply. 3-9,12-16 In addition, endoscopic endonasal approaches were designed to avoid ON traction.…”
mentioning
confidence: 99%